A Socialização no Contexto de Projetos Esportivos: um estudo de caso na Fundação Gol de Letra - Barbirato, Fernanda Rosa (2006)
ABSTRACT This work approaches the process of socialization through the sport, in order to argue the signification of values that can be appropriate for educating by me ans of the practical sporting. From the presentation of two proposals of the socialization process - imposed or constructed - it could be verified the influences that permeate the relation individual-society and be delineated the social representations concerning the sport. To assist in this analysis of values, it was opted to the crossing of you arrive in port them theoretical produced for authors as Durkheim, Berger, Coulon, Elias, Bourdieu, Vygotsky and Geertz, amongst others. Moreover, the epistemologic al quarrel of the referring physical education to the critical ones on the shock was presented all enters the educative sport in opposition to the income sport. Ahead of all these information, were developed a study of case in the Fundação Gol de Letra, from three focus of research - the institution, the student and its families - to verify possible accories and dissonances front to a proposal pedagogical who if make use to adopt an educative sport to socialize children and adolescents, through the access to the corporal culture of movement. The conclusions send to a picture where if it can verify the force that where if it can verify the force that the primary socialization presents on the students, besides demonstrating that the meanings associates to the sport result of the joint influence of some instances.